The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2022
DOI: 10.1186/s12889-022-14863-6
|View full text |Cite
|
Sign up to set email alerts
|

“In times of stress, it is good to be with them”: experience of dog owners from a rural district of Sri Lanka

Abstract: Background The dog has been man’s best companion since ancient times. And, dog ownership is associated with improved physical activity and cardiovascular health. We aim to explore the experience of dog owners on dog ownership and its effects on personal and family health in Anuradhapura, Sri Lanka. Such studies are scarce in developing countries and rural regions. Methods A qualitative study was conducted using in-depth interviews with dog owners i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Severe or prolonged stress can lead to various psychological and physiological problems ( Iwata et al, 2013 ). Companion animals have a beneficial effect on moderating human stress levels ( Janssens et al, 2021 ; Junça-Silva et al, 2022 ; Rathish et al, 2022 ), especially for individuals in high-stress work environments ( Cevizci et al, 2012 ). Companion animals often play an important role as attachment figures in human lives ( Sable, 2013 ).…”
Section: Studies On Companion Animals Improving Human Psychological H...mentioning
confidence: 99%
“…Severe or prolonged stress can lead to various psychological and physiological problems ( Iwata et al, 2013 ). Companion animals have a beneficial effect on moderating human stress levels ( Janssens et al, 2021 ; Junça-Silva et al, 2022 ; Rathish et al, 2022 ), especially for individuals in high-stress work environments ( Cevizci et al, 2012 ). Companion animals often play an important role as attachment figures in human lives ( Sable, 2013 ).…”
Section: Studies On Companion Animals Improving Human Psychological H...mentioning
confidence: 99%
“…At a time when the world was under the effects of the pandemic, interesting experiences were published such as an article based on observations in rural populations of Sri Lanka, where it was observed that dog ownership is related to family behaviors that promote their health and that of their communities [24]. Rathish et al conclude that it is essential to have background information on the effects of a pet dog on personal and family health to implement One Health via human-animal interaction.…”
Section: Do Dogs Have a Place In Palliative Care?mentioning
confidence: 99%